Triterpene Compound from Ethyl Acetate Fraction of Kesambi Bark (Schleichera oleosa) and Its Activity as Anti-Bacterial - Musa, Weny J.A.; Setiyandani, Kurnia Indah; Mustafid, Afif Hidayatul; Bialangi, Nurhayati; Situmeang, Boima (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
In our earlier study, we managed to find the antibacterial activity of the ethyl acetate fraction of the kesambi bark stem. In our next study, we isolated secondary metabolite compounds from the ethyl acetate fraction of the kesambi stem bark and tested the antibacterial activity of isolates against the bacteria Escherichia coli and Staphylococcus aureus. Separation is carried out by the method of column chromatography. Analysis of stain patterns and purity was performed with thin-layer chromatography (TLC). The test of antibacterial activity was carried out by the Kirby Bauer method. Characterization of pure isolates was performed with IR, 1H -NMR, 13C -NMR and DEPT 135° spectroscopy. The results of the characterization of pure isolates show that the isolated compound is a triterpenoid compound with the name IUPAC compound lup-20(29)-en-3-ol. The results of antibacterial tests showed that the compound lup-20(29)-en-3-ol has antibacterial activity against E. coli and S. aureus which is relatively moderate.